2023
DOI: 10.1111/jdi.13986
|View full text |Cite
|
Sign up to set email alerts
|

A newly developed glucagon sandwich ELISA is useful for more accurate glucagon evaluation than the currently used sandwich ELISA in subjects with elevated plasma proglucagon‐derived peptide levels

Abstract: Aims/Introduction: Glucagon, a peptide hormone produced from proglucagon, is involved in the pathophysiology of diabetes. Plasma glucagon levels are currently measured by sandwich enzyme-linked immunosorbent assay (ELISA), but the currently used sandwich ELISA cross-reacts with proglucagon-derived peptides, thereby providing incorrect results in subjects with elevated plasma proglucagon-derived peptide levels. We aimed to develop a more broadly reliable ELISA for measuring plasma glucagon levels. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…We have previously reported that the Mercodia sandwich ELISA yields falsely elevated plasma glucagon levels post-pancreatectomy due to the increased presence of glicentin in patients’ plasma [ 7 ]. A similar phenomenon was observed in patients who underwent bariatric surgery (gastric sleeve resection) [ 8 ]. Therefore, although Mercodia sandwich ELISA is more accurate than the conventional competitive RIA, it may provide incorrect glucagon values after resection of the pancreas or stomach.…”
Section: Development Of a New Glucagon Sandwich Elisa With Higher Spe...supporting
confidence: 74%
See 3 more Smart Citations
“…We have previously reported that the Mercodia sandwich ELISA yields falsely elevated plasma glucagon levels post-pancreatectomy due to the increased presence of glicentin in patients’ plasma [ 7 ]. A similar phenomenon was observed in patients who underwent bariatric surgery (gastric sleeve resection) [ 8 ]. Therefore, although Mercodia sandwich ELISA is more accurate than the conventional competitive RIA, it may provide incorrect glucagon values after resection of the pancreas or stomach.…”
Section: Development Of a New Glucagon Sandwich Elisa With Higher Spe...supporting
confidence: 74%
“…As shown in the bottom panel of Fig. 5 , cross-reactivity tests revealed almost no cross-reactivity with glucagon-related peptides, including glicentin, in the new sandwich ELISA, a striking contrast to the Mercodia sandwich ELISA, which showed cross-reactivity (at several percentage points) with other peptides [ 8 ]. The newly developed sandwich ELISA also showed a close correlation with LC-MS/MS ( Fig.…”
Section: Development Of a New Glucagon Sandwich Elisa With Higher Spe...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, Kobayashi et al recently revealed a significant issue with cross-reactivity in the conventional ELISA method, particularly in subjects with elevated plasma proglucagon-derived peptide levels [ 164 ]. This cross-reactivity might lead to incorrect results and, consequently, potential misinterpretation of blood glucagon levels from previous clinical data using traditional glucagon assays, which should be revisited and re-evaluated.…”
Section: Discussionmentioning
confidence: 99%